Antimicrobial and molecular interaction studies on derivatives of curcumin against Streptococcus pneumoniae which caused pneumonia - Li,Liang-Mei (Pontificia Universidad Católica de Valparaíso, 2016)
Background: The antimicrobial properties and molecular interaction analysis of curcumin and its derivatives against three different strains of Streptococcus pneumoniae (Penicillin-susceptible, Penicillin-intermediate and Penicillin-resistant) are studied. Results: These properties were analyzed based on the measurement of the inhibition zone, minimum inhibitory concentration (MIC), and rate of kill revealed that curcumin monoglucoside, curcumin diglucoside and curcumin possessed strong antimicrobial properties even on the Penicillin-resistant strains. Additionally, the molecular docking simulation analyses against Penicillin Binding Protein of S. pneumoniae also confirm that these compounds docked at the active site of the enzyme. Further, the molecular dynamics simulation validates the conformational stability of the docked ligand-protein complexes in the dynamic environment. Conclusion: curcumin monoglucoside, curcumin diglucoside and curcumin can be prescribed for treatment against Penicillin-resistant S. pneumoniae.